Mechanisms and Evolution of Oxidative Sulfur Metabolism in Green Sulfur Bacteria - Gregersen, Lea H.; Bryant, Donald A.; Frigaard, Niels-Ulrik (Frontiers in Microbiology, 2011)
Green sulfur bacteria (GSB) constitute a closely related group of photoautotrophic and thiotrophic bacteria with limited phenotypic variation. They typically oxidize sulfide and thiosulfate to sulfate with sulfur globules as an intermediate. Based on genome sequence information from 15 strains, the distribution and phylogeny of enzymes involved in their oxidative sulfur metabolism was investigated. At least one homolog of sulfide:quinone oxidoreductase (SQR) is present in all strains. In all sulfur-oxidizing GSB strains except the earliest diverging Chloroherpeton thalassium, the sulfide oxidation product is further oxidized to sulfite by the dissimilatory sulfite reductase (DSR) system. This system consists of components horizontally acquired partly from sulfide-oxidizing and partly from sulfate-reducing bacteria. Depending on the strain, the sulfite is probably oxidized to sulfate by one of two different mechanisms that have different evolutionary origins: adenosine-5’-phosphosulfate reductase (APR) or polysulfide reductase-like complex 3 (PSRLC3). Thiosulfate utilization by the SOX system in GSB has apparently been acquired horizontally from proteobacteria. SoxCD does not occur in GSB, and its function in sulfate formation in other bacteria has been replaced by the DSR system in GSB. Sequence analyses suggested that the conserved soxJXYZAKBW gene cluster was horizontally acquired by Chlorobium phaeovibrioides DSM 265 from the Chlorobaculum lineage and that this acquisition was mediated by a mobile genetic element. Thus, the last common ancestor of currently known GSB was probably photoautotrophic, hydrogenotrophic, and contained SQR but not DSR or SOX. In addition, the predominance of the Chlorobium-Chlorobaculum-Prosthecochloris lineage among cultured GSB could be due to the horizontally acquired DSR and SOX systems. Finally, based upon structural, biochemical, and phylogenetic analyses, a uniform nomenclature is suggested for sqr genes in prokaryotes.